Fran O’Rourke’s Joyce, Aristotle, and Aquinas - Farrell, Thomas J. (New Explorations, 2023)
In my review, I highlight the Irish philosopher and singer Fran O’Rourke’s new massively learned and massively researched and admirably lucid 2022 book Joyce, Aristotle, and Aquinas. However, I discuss his account of Western philosophy in the larger conceptual framework of media ecology by drawing on the work of the Canadian Renaissance specialist and media ecology theorist Marshall McLuhan (1911-1980; Ph.D. in English, Cambridge University, 1943), the American Jesuit Renaissance specialist and media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955), and the American-born Joyce specialist and media ecology theorist Eric McLuhan (1942-2018; Ph.D. in English, University of Dallas, 1982).